Electrically evoked compound action potentials in cochlear implant users with preoperative residual hearing - Liebscher, Tim; Hornung, Joachim; Hoppe, Ulrich (Frontiers in Human Neuroscience, 2023)
Introduction: Residual hearing in cochlear implant (CI) candidates requires the functional integrity of the nerve in particular regions of the cochlea. Nerve activity can be elicited as electrically evoked compound action potentials (ECAP) after cochlear implantation. We hypothesize that ECAP thresholds depend on preoperative residual hearing ability.Materials and methods: In a retrospective study, we analyzed 84 adult cochlear implant users who had received a Nucleus ® CI632 Slim Modiolar Electrode and who preoperatively had had residual hearing. Inclusion criteria were severe to profound hearing loss with preoperative measurable hearing in the ear to receive the implant, postlingual hearing loss, German as native language and correct placement of the electrode, inserted completely into the scala tympani. Electrically evoked compound action potential (ECAP) was recorded intraoperatively. The angular insertion was measured for each electrode contact from postoperative computed tomography to estimate the corresponding spiral ganglion frequency. Pure-tone audiometry and allocated ECAP thresholds were tested to investigate possible correlation.Results: The average of hearing thresholds, tested at 0.5, 1, 2, and 4 kHz (4FPTA) was 82±18 (range 47-129) dB HL. The success rate for recording ECAP thresholds was 96.9%. For all comparable pure-tone frequencies (1, 2, 4 and 8 kHz), there was significant correlation between preoperative hearing levels and intraoperative ECAP thresholds (p < 0.001). Higher hearing thresholds are associated with increased ECAP thresholds. Conclusion: In CI candidates with adequate residual hearing, intraoperative electrophysiological measurement records lower thresholds. This outcome may be explained by the neural survival density of the peripheral system, with less neural degeneration.